2021
DOI: 10.1177/10406387211020117
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for electrophoretograms obtained by capillary electrophoresis of dialyzed urine from healthy dogs

Abstract: Electrophoresis of urine to evaluate protein fractions in dogs with proteinuria to differentiate glomerular from tubular damage has increased in recent years; however, capillary electrophoresis (CE) of urine has not been reported in a study of > 40 healthy animals, to our knowledge. We aimed to establish reference intervals (RIs) for the urine protein fractions obtained by CE of urine from healthy dogs. We obtained urine samples from 123 clinically healthy dogs of both sexes between December 2016 and April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies that performed gel electrophoresis in urine from healthy individuals have found that this fraction contains proteins related to the defense of the urinary tract. According to previous studies, the Tamm-Horsfall protein or uromodulin is usually excreted in healthy individuals due to its protective properties against lower urinary tract infections [8,29,37]. The high-resolution electrophoresis technique detected that one of the major proteins in the urine of healthy cats was uromodulin [29], so this protein could be excreted in a higher proportion in the F4 urinary fraction in the feline species.…”
Section: Comparison Between the Urinary Electrophoretograms Of Dogs A...mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies that performed gel electrophoresis in urine from healthy individuals have found that this fraction contains proteins related to the defense of the urinary tract. According to previous studies, the Tamm-Horsfall protein or uromodulin is usually excreted in healthy individuals due to its protective properties against lower urinary tract infections [8,29,37]. The high-resolution electrophoresis technique detected that one of the major proteins in the urine of healthy cats was uromodulin [29], so this protein could be excreted in a higher proportion in the F4 urinary fraction in the feline species.…”
Section: Comparison Between the Urinary Electrophoretograms Of Dogs A...mentioning
confidence: 99%
“…UCE was performed according to the standardized method described by Navarro et al (2021). Urine was dialyzed before CE to eliminate salts and compounds that could interfere with the wavelength used for reading and cause artifact peaks.…”
Section: Urinary Capillary Electrophoresismentioning
confidence: 99%
See 2 more Smart Citations